Braiding the Ropes: Adding Second or Additional Language Acquisition to Reading and Writing Metaphors - Jennifer M. Lane; Teresa J. Kennedy (MDPI AG, 2024)
Drawing on second language acquisition theories and existing visuals, this article proposes a new educational metaphor, Lane's L2+ Acquisition Rope, to encompass the complexities of second or additional language learning. This metaphor integrates five major strands-external factors, social factors, affective factors, innate factors, and internal factors-to provide a comprehensive framework for understanding proficient second language acquisition. Implications of this visual highlight the importance of incorporating socio-cultural, neurological, and affective dimensions into educational metaphors to support diverse learners effectively. Lane's L2+ Acquisition Rope offers a promising avenue for educators to enhance instructional practices and promote equitable learning outcomes for English Language Learners and other student subgroups.